The joint effect of firm capability and access to finance on firm performance among small businesses: A developing country perspective - Turyakira, Peter; Kasimu, Sendawula; Turyatunga, Pedson; Nakyejwe Kimuli, Saadat (African Journal of Business Management, 2019)
The purpose of this paper was to establish the joint effect of access to finance and firm capability on small businesses’ performance in Kampala, Uganda. The study adopted a cross-sectional design with a sample of 384 small businesses. Self administered questionnaires were used in data collection and data was collected from August to November 2018. The study utilised SPSS to perform correlation and regression. The study found out that access to finance, firm capability and firm performance are positively related. Regression analysis also revealed that access to finance and firm capability equally account for 41.8% change in small business performance. Conversely, access to finance was found to be the most influential factor in predicting firm performance as compared to firm capability. Therefore, the study recommends that policies and programs to improve small business owners’ capabilities should be implemented to enhance the performance of their firms; small business owners need government support to get finance characterised by low interest rates; no collateral security and as such, their performance will gradually improve. Small business owners also need to establish long-tern relationships with customers, suppliers and employees to improve their services and products to better the performance of their firms.
Keywords: Firm capability; Access to finance; Firm performance; Small businesses